Adsorption of Trinitrotoluene on a MgO(001) Surface Including Surface Relaxation Effects. (23rd August 2012) - Guerra, Thiago; Borges, Itamar
Abstract : A thorough investigation of 2, 4, 6-trinitrotoluene (TNT) adsorption on a MgO(001) surface was carried out using density functional theory (DFT) combined with periodic boundary conditions. Four different initial orientations of the TNT molecule, adsorbed on two different representations of the MgO(001) surface, were investigated. In the first surface representation, there were two fixed layers of atoms and in the second the surface had three layers, with the uppermost fully relaxed in geometry optimizations. Electron density difference maps for each case were computed and provided a detailed picture of the interactions. The results showed a physical adsorption process for both surface representations. In the most favorable situation—TNT adsorbed on the surface with three layers—the computed adsorption energy was −9.89 kcal/mol. The importance of allowing the uppermost layer of the surface to fully relax upon molecular desorption was shown.